A formação para docência em administração no Brasil: os saberes docentes em uma universidade de fronteira - Sobral, Rosely Cândida (2019)
It investigates how the teacher training occurs in administration in Brazil and the effects on teachers' knowledge mobilized by teachers of a course, in a frontier context. The question that guides the research is: how the teacher training is treated in the academic master’s programs in Brazil and what are the reflexes in the teachers' knowledge in a frontier university? The issue is announced to meet the following specific objectives: to analyze the teacher training process in the Academic Master Programs in Administration in Brazil; to analyze in political projectsmanagement course pedagogical at frontier universities if there is any specificity related to the frontier; investigate the process of professional training of teachers of an administration course at a frontier university and understand what are the knowledge and knowledge that undergraduate teachers in administration mobilize in the pedagogical action. From the concepts of teacher training and the teaching knowledge model proposed by Tardif (1991) analyzes the programs of academic master’s in administration if they offer disciplines of teacher training in their curriculum. Conducts a semi-structured interview with 3 faculty members of the Unioeste campus of Foz do Iguaçu. It shows that teacher training is built by classroom practice, but that the teaching stage is important in this process. That knowing curricular knowledge does not exist a look at local issues such as border issues. It concludes that the training of teachers in Administration is not given in the programs of Academic Master in Administration, considering that only the professional knowledge and curricular are not sufficient for the construction of the pedagogical practice. And that even in curriculum analyses there is no concern with frontier knowledge (local knowledge) because this is not valued, neither in the interviews, nor in the pedagogical political projects of the courses of Administration nor in the programs analyzed. The results point to a teaching training model that considers plural knowledge and rethinks the importance of teacher training in academic master’s programs in administration in Brazil.